(3TQM GdeQGcTi Ydi GdeXheI GdefShHI ddaRGQi GdTgjQ HGHf GdeLQGO aj EYQGH GdLeds - (3EHQGgje Hf GdMSf GdeQGcTis; (3CHh YHO Gddg eMeO Hf eMeO Hf eMeO Hf YeQGf GdaRGQj GdSdGhj GdeLQGOj, GHf GdeLQGOj,J (B778 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3bGd GdTjN GdYGde gPG TQM ddbUjOI GdefShHI ddTjN GdabjI GdfMhi SjOi eMeO Hf eMeO Hf YeQGf GdaRGQi GdTgjQ HGHf GdeLQGO GdSdGhi Ydi EYQGH GdLed s
(3BNQgG (B:s
(3hbO ced GdebUhO eeG CQOJg , addg QHi GdMeO OGFekG ced TQM GdbUjOI hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs